Kant’s Apriorical Idea of Law: Two Ways of its Justification - Wojciech Załuski (Acta Universitatis Lodziensis Folia Iuridica, 2023)
Kant proposed an apriorical account of the idea of law, according to which the law’s only legitimate goal is to guarantee for each citizen a possibly broad scope of external freedom compatible with the same scope of all other citizens. However, Kant did not make it entirely clear how this idea is to be justified. This paper presents two ways of justification, drawing on Kant’s view of the human nature. The first one appeals to the apriorical components of this view (rationality, freedom, equality, and dignity), and the second one is based on its empirical components (the ambivalent account of human predispositions).